宫女三千合宫弃 ：白居易和元稹的宫女题材诗歌研究 = A study of the poems about palace maids by Bai Juyi and Yuan Zhen - 林婉琪 Lam, Yuen Kay (2011)
在唐代的社会中，宫女地位卑微，其命运都是由君王或其他当权者所摆布，造成了宫女本身悲惨的结局。若得不到皇上的宠幸，她们的后半生将会是一场悲剧。宫女的遭遇也是唐代许多诗歌的题材。诗人把宫女的情感及遭遇叙写出来，不但为宫女诉说了她们的故事，有些诗人更是借由诗歌发表自己的心声。白居易和元稹都是唐代著名的诗人，他们俩也写了有关宫女题材的诗篇，其中的一些被列为“讽喻诗歌”，对后代更是有很大的影响。其中《上阳白发人》是两位诗人新乐府诗歌的同题之作，描述着宫女入宫后因得不到君王的青睐而被幽禁在上阳宫，而其中的辛酸和悲情无人能了解。本文将会描述唐代宫女的背景和命运，并通过白居易和元稹的宫女题材诗歌中一探中国古代社会里宫女女性形象的结构及结局。笔者也将会比较白居易和元稹的同题诗歌《上阳白发人》，希望藉由诗歌的写作背景、内容主题和艺术特色上的异同更深入地探讨宫女的悲剧。During the Tang Dynasty, palace maids were of a low status. The emperor or those in authority wielded immense power over their fate, causing great misery to the palace maids. If the ruling emperor did not bestow his favour upon them, the palace maids were condemned to tragic lives. The life experiences of palace maids were also a popular theme for many Tang poems. In describing the emotions and encounters of palace maids, these poets helped the palace maids tell their life stories. In addition, these poets also expressed their deepest personal thoughts through these poems. Bai Juyi and Yuan Zhen were two of the most famous poets in the Tang Dynasty. Both wrote poems related to the theme of palace maids. Some of their work were also classified as allegorical poems and had a great influence on future generations. Two of their poems on palace maids share a common title: “Shang Yang White-hair Elders” (Shang Yang Bai Fa Ren) and describe how the palace maids were unable to win the Emperor’s favour after entering the palace. They were thus imprisoned at the Shang Yang Palace and experienced sorrows and grief that no one can ever understand. This thesis will portray the background and fate of palace maids in the Tang Dynasty. In addition, Bai Juyi and Yuan Zhen’s poems will also be analysed to enhance the understanding of the image and fate of palace maids in ancient Chinese society. The two poems entitled “Shang Yang Bai Fa Ren” will be compared in terms of their background, themes and artistic features, this will lead to a better understanding of the palace maids’ tragedies.